Temperature, Albedo, and Emissivity of Triton and Proteus from Voyager 2 IRIS Data - Garrett Nobis; Vincent Chevrier (The Planetary Science Journal)
The Voyager 2 infrared interferometer and spectrometer (IRIS) spectra for Triton are revisited, and the Proteus IRIS spectra are looked at for the first time. Fifty more spectra are added to the average of 16 previously used for Triton. The unit emissivity Planck function temperature result is 37.9  ±  0.5 K. Iterating IRIS temperatures over several emissivities allows for constraints on emissivity and Bond albedo based on past data. Upper and lower bounds on Triton’s temperature and albedo of 37.9  ±  0.5 to 46.1  ±  0.7 K for temperature and 0.67−0.86 for albedo are determined from the IRIS data and previous albedo results. For Proteus, the surface temperature is found to be 47.4  ±  0.7 K, along with an emissivity from ∼0.75 to 1 and Bond albedo between 0.2 and 0.3.